2013
DOI: 10.1515/cclm-2012-0422
|View full text |Cite
|
Sign up to set email alerts
|

The Asian project for collaborative derivation of reference intervals: (2) results of non-standardized analytes and transference of reference intervals to the participating laboratories on the basis of cross-comparison of test results

Abstract: Background: The 2009 Asian multicenter study for derivation of reference intervals (RIs) featured: 1) centralized measurements to exclude reagent-dependent variations; 2) inclusion of non-standardized analytes (hormones, tumor makers, etc.) in the target; and 3) cross-check of test results between the central and local laboratories. Transferability of centrally derived RIs for non-standardized analytes based on the cross-check was examined. Methods: Forty non-standardized analytes were centrally measured in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
35
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 5 publications
9
35
2
Order By: Relevance
“…Therefore, LAVE method was applied in our study to exclude individuals with abnormal results in other related analytes, apparently attributable to those conditions. The performance of the LAVE method have been well characterized in previous reports [14,15] and this study confirmed the need for its use in seven out of nine test items shown in Figure 1. This study also confirmed that RIs by the NP method were easily influenced by latent abnormal results for those test items compared with the RIs derived by the P method.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, LAVE method was applied in our study to exclude individuals with abnormal results in other related analytes, apparently attributable to those conditions. The performance of the LAVE method have been well characterized in previous reports [14,15] and this study confirmed the need for its use in seven out of nine test items shown in Figure 1. This study also confirmed that RIs by the NP method were easily influenced by latent abnormal results for those test items compared with the RIs derived by the P method.…”
Section: Discussionsupporting
confidence: 83%
“…The tests results were evaluated by using the same statistical methods described in the previous studies [12][13][14][15] but are described briefly below. …”
Section: Discussionmentioning
confidence: 99%
“…As in their previous study [ 11 ] they limited the component of inter-laboratory variability by centralizing analyzes of deep-frozen sera of volunteers from 63 participating laboratories (in Japan and South-East Asia) in a single laboratory in Japan. Significant regional differences were identified for 11 analytes.In the second study [ 10 ] volunteers were recruited from 48 laboratories in 14 cities in Japan and 15 laboratories in nine cities in South-East Asia. Analyses of deepfrozen sera of patients were centralized in a single laboratory in Japan, following the same protocol as in the first study.…”
mentioning
confidence: 99%
“…In the second study [ 10 ] volunteers were recruited from 48 laboratories in 14 cities in Japan and 15 laboratories in nine cities in South-East Asia. Analyses of deepfrozen sera of patients were centralized in a single laboratory in Japan, following the same protocol as in the first study.…”
mentioning
confidence: 99%
See 1 more Smart Citation